2003
DOI: 10.1210/jc.2002-021251
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Biochemical Tests for Pheochromocytoma: Measurement of Fractionated Plasma Metanephrines Compared with the Combination of 24-Hour Urinary Metanephrines and Catecholamines

Abstract: We compared the diagnostic efficacy of fractionated plasma metanephrine measurements to measurements of 24-h urinary total metanephrines and catecholamines in outpatients tested for pheochromocytoma at Mayo Clinic Rochester from January 1, 1999, until November 27, 2000. Catecholaminesecreting tumors were histologically proven. The sensitivity of fractionated plasma metanephrines was 97% (30 of 31 patients), compared with a sensitivity of 90% (28 of 31) for urinary total metanephrines and catecholamines (P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
260
2
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(287 citation statements)
references
References 20 publications
7
260
2
12
Order By: Relevance
“…The diagnosis is made by the measurement of urinary catecholamines and the identification of tumor by CT scanning, magnetic resonance imaging, or radionucleotide scanning with MIBG or octreotide [18]. Since 90% of the cases are derived from the adrenal medulla, the measurement of the levels of urinary metanephrine, a metabolite of E, is thought to be a sensitive biochemical screening test [19][20][21][22]. In the present case, we found an elevation of urinary normetanephrine, but not metanephrine levels and failed to locate the suspected adrenal tumor on either side.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is made by the measurement of urinary catecholamines and the identification of tumor by CT scanning, magnetic resonance imaging, or radionucleotide scanning with MIBG or octreotide [18]. Since 90% of the cases are derived from the adrenal medulla, the measurement of the levels of urinary metanephrine, a metabolite of E, is thought to be a sensitive biochemical screening test [19][20][21][22]. In the present case, we found an elevation of urinary normetanephrine, but not metanephrine levels and failed to locate the suspected adrenal tumor on either side.…”
Section: Discussionmentioning
confidence: 99%
“…These are constantly produced by the actions of catechol-O-methyltransferase on catecholamines leaking from stores within tumour cells and, therefore, show more consistent increases above normal in patients with phaeochromocytoma than plasma catecholamines, making this the more reliable test in these circumstances. [17][18][19][20] There is, however, still the possibility of false-positive results in which levels of metabolites are above the upper limit of normal, but not high enough to definitely diagnose phaeochromocytoma. Eisenhofer et al 6 have shown that, in such cases, clonidine suppression testing combined with measurement of plasma metanephrines can distinguish true-from false-positive results.…”
Section: Evaluation Of Clonidine Suppression Test CM Mchenry Et Almentioning
confidence: 99%
“…Our case shows that EUS-guided puncture of pheochromocytoma may evoke an abrupt release of catecholamines, and subsequently, a lifethreatening hypertensive crisis, similar to the well-known risk of percutaneous biopsy [2]. Based on this case, we advise exclusion of (subclinical) pheochromocytoma before all EUS-guided punctures of adrenal lesions, by 24-h urine collection for metanephrines and catecholamines [7]. A heterogeneous mass of almost 5 cm with a hypoechogenic center was seen in the right adrenal gland.…”
mentioning
confidence: 91%